Mucocele in atypical localization - a case report - Damian Chybicki; Anna Janas-Naze; Piotr Osica (Kazimierz Wielki University, 2019)
The article describes a case of an oral mucocele of the palatoglossal arch in 5 y.o. patient, treated by conventional surgical excision of the lesion in general anesthesia.